Sketch as a Documentary Source for Attribution of Altai Stone-Cutting Products of the Late 18th Century - Borovkova, Natalia V. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2022)
This article studies one of the relevant issues of Russian stone-cutting arts of the turn of the nineteenth century, i.e. the problems of attribution of Altai stone-cutting works. The author carries out a comparison of graphic materials with images of stone-cutting products from the Lokot’ Altai Factory. The author singles out sets of images of stone objects from the Lokot’ Stone-Cutting Factory kept in the funds of the State Hermitage Museum and the Altai State Museum of Local Lore, which makes it possible to get a more comprehensive idea of the history of the development of Russian stone-cutting art, dispel persistent myths, and shed light on the activity of an almost forgotten unique production. Particular attention is paid to the organisation of stone-cutting production in Russia starting with the second half of the eighteenth century, as well as the administration of the Kolyvan’ factories in the management system of the Cabinet of His Imperial Majesty. The author closely examines the system of orders, production, and performance of Russian grinding factories. For the first time in this research field, much attention is paid to the systems of documenting every step of stone-cutting production from the stonecutters to presentation to customers. The author confirms the fact that the Lokot’ Factory used already tested projects of the Peterhof Granite Factory as samples for their production. The article presents drawings of stone objects made during the work of the Lokot’ Polishing Factory in the Kolyvano-Voskresensky mountain district of Altai. The results of this scholarly research may be used to conduct an examination of objects of decorative and applied art. In the course of the study, it is proposed to distinguish between two periods in Altai stone-cutting art: Lokot’ (1786–1799) and Kolyvan’ (1802 — present) and based on the collected graphic materials attribute the works of two stone-cutting enterprises of Altai of the late eighteenth — nineteenth centuries. The graphic materials referred to in the study are an array of historical and archival sources of a high documentary value for the attribution of stone-cutting products made by Altai masters.